Analysis of blood culture results between 2019-2022 in Bayburt province - Kayali, Sümeyra (Refik Saydam National Public Health Agency (RSNPHA), 2025)
Objective: Blood culture is the gold standard in the diagnosis of bloodstream infections and allows the isolation of microorganisms and antibiotic susceptibility tests. The aim of this study is to determine the distribution and antibiotic resistance profile of microorganisms isolated from blood cultures and to guide empirical treatment. Methods: Blood culture results of Bayburt State Hospital Microbiology Laboratory between May 2019 and May 2022 were retrospectively reviewed and included in the study. Blood cultures were incubated in the BacT/ ALERT (BioMérieux, Marcy l’Etoile, France) automated system. Vials with positive signals were inoculated on chocolate agar, 5% sheep blood agar and eosin methylene blue (EMB) agar and incubated at 37°C for 24-48 hours. Bacterial identification was performed by conventional methods and antibiotic susceptibility was determined by disk diffusion method. Results: There was no growth in 3,778 (77.1%) of 4,902 blood cultures accepted to the laboratory. Of the 1,124 (22.9%) blood cultures that grew, 860 (76.5%) grew gram positive bacteria, 244 (21.7%) grew gram negative bacteria and 20 (1.8%) grew yeast type fungi. The skin flora elements were analyzed for contamination and the contamination rate was 9.9% (n:488/4,902). The gram positive bacteria detected were coagulase-negative staphylococci, Staphylococcus aureus and Enterococcus spp in order of frequency. Gram-negative bacteria were Escherichia coli, Klebsiella spp, Enterobacter spp, Brucella spp, Acinetobacter spp, Proteus spp, Pseudomonas spp and Citrobacter spp. While susceptibility rates to penicillin, cephalosporin, quinolone group antibiotics and trimethoprim-sulfamethoxazole were below 50% in Enterobacteriaceae family, susceptibility rates to carbapenem and aminoglycoside group antibiotics imipenem and amikacin were above 50%. Sixty percent of coagulase-negative staphylococci and 20% of S. aureus isolates were methicillin resistant. All Enterococcus spp isolates were susceptible to vancomycin, teicoplanin and linezolid. Conclusion: In Bayburt province, vancomycin is a reliable option for empirical treatment of grampositive bacteria due to the presence of methicillinresistant staphylococcal isolates and the susceptibility of enterococcal isolates to vancomycin. In addition, aminoglycoside and carbapenem group antibiotics would be better choices than penicillin and cephalosporin group antibiotics for gram negative agents. Such cumulative antibiotic susceptibility data are instructive for empirical treatment and lead to rational antibiotic use. © Bu eser Creative Commons Alıntı-GayriTicari-Türetilemez 4.0 Uluslararası Lisansı ile lisanslanmıştır.
Bayburt ili 2019-2022 yılları arası kan kültürü sonuçlarının analizi
Keywords: anti-bacterial agents; Blood culture; retrospective study; sepsis